Employment and labour markets : some issues for the new millennium - Gregory, M (Emerald Group Publishing Ltd, 2000)
The deteriorating labour market position of low-skilled workers challenges economic efficiency and social equity. Four aspects are examined: joblessness among the low-skilled; the prevalence of low pay among women; persistence in low pay; and the overlap between low pay and household poverty. It concludes that the labour market institutions of "social Europe" are effective in reducing the disadvantage of vulnerable groups, although they have protected women less effectively than men. Education and training will have an important contribution to make; more immediately, reducing the deflationary bias in European macroeconomic policies should benefit the low-paid.